Gauging the Potential for Integrating Paratransit Operators Into the Dar es Salaam BRT Feeder System through Own Capital (Tanzania Journal for Population studies and Development, 2013)
An efficient urban transport is very important in providing mobility to an increasing urban population and sustaining urban economic development. Public transport service in Dar es Salaam city is mostly provided by paratransit or small capacity buses (daladalas), whose service are poor with low comfort, security, safety and convenience. To alleviate the situation, the City is planning for a city Bus Rapid Transit (BRT) system that will displace the existing paratransit operators from the earmarked corridors. This paper evaluates the potential for the paratransit operators to provide services in the less capital and specification demanding feeder system of the BRT. It is argued that paratransit owners, organised in companies or cooperatives, can raise enough capital to purchase the specified number of feeder buses by either contributing own money or selling their vehicles. It is concluded that there is a high potential for the existing paratransit operators to be integrated into the BRT feeder system through their own capital.